2022
DOI: 10.3390/tomography8050202
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Imaging Features of COVID-19 Pneumonia Caused by the Delta (B.1.617.2) and Omicron (B.1.1.529) Variant in a German Nested Cohort Pilot Study Group

Abstract: Background: The aim of this study was to evaluate CT (computed tomography) imaging differences for the Delta and the Omicron variant in COVID-19 infection. Methods: The study population was derived from a retrospective study cohort investigating chest CT imaging patterns in vaccinated and nonvaccinated COVID-19 patients. CT imaging patterns of COVID-19 infection were evaluated by qualitative and semiquantitative scoring systems, as well as imaging pattern analysis. Results: A total of 60 patients (70.00% male,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
(35 reference statements)
1
16
0
Order By: Relevance
“…The pneumonia lesion occurred at a median of 3 days after admission, peaked within 3 to 7 days after onset, and then began to be absorbed. Compared with the Omicron subvariant BA.2 previously studied in children (15), we found that the Delta variant had more extensive lung involvement and caused more extensive parenchymal changes on chest CT images, which was basically consistent with other emerging studies (5,18,19). However, CT images of pneumonia lesions in Delta and Omicron appear to be milder and less recognizable than those in WT and Alpha (17).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The pneumonia lesion occurred at a median of 3 days after admission, peaked within 3 to 7 days after onset, and then began to be absorbed. Compared with the Omicron subvariant BA.2 previously studied in children (15), we found that the Delta variant had more extensive lung involvement and caused more extensive parenchymal changes on chest CT images, which was basically consistent with other emerging studies (5,18,19). However, CT images of pneumonia lesions in Delta and Omicron appear to be milder and less recognizable than those in WT and Alpha (17).…”
Section: Discussionsupporting
confidence: 89%
“…The application of clinical and CT imaging knowledge based on WT to guide the evaluation and treatment of Omicron variant-induced pneumonia may lead to certain bias. Furthermore, several recent cross-sectional studies have demonstrated that the Omicron variant shows fewer, less severe, and more "atypical" lesions on chest CT than the Delta variant (5,18,19). Despite differences and inconsistencies, Delta is still likely to be closest to Omicron in terms of timing of occurrence, vaccination status, and clinical and imaging features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tube current modulation CARE Dose4D at quality reference mAs of 100mAs and automatic tube voltage setting with CARE kV at 120kV reference with a collimation of 128x0.6mm was used. Depending on the clinical question that needed to be answered intravenous contrast agent was applied, as detailed elsewhere [11,12]. In cases with follow-up CT scans, only the rst acquired CT scan was evaluated.…”
Section: Ct Examinationmentioning
confidence: 99%
“…Following the identi cation of the study cohort via the electronic hospital information system, pertinent clinical data were gathered from the electronic patient records. This data compilation included vaccination status, demographic particulars (age, sex), details of infection (including virus variant and symptom onset, COVID-19 antibodies), symptomatology (dyspnea, coughing, fever), pre-existing conditions (such as Body Mass Index (BMI) and pre-existing illnesses), laboratory parameters (C-reactive protein (CRP), procalcitonin (PCT), D-Dimer, PTT, INR, platelets, creatinine, urea, AST, ALT, pO2, pCO2), results of CT scans (quantitative score of chest CT lesions as detailed elsewhere (Askani et al, 2022(Askani et al, , 2023), speci cs of COVID-19 treatment (ICU admission, ICU duration, oxygen therapy), and any complications (sepsis, pulmonary superinfection, coagulopathy, pulmonary artery embolism, renal failure, mortality) that occurred.…”
Section: Data Acquisitionmentioning
confidence: 99%